Pressure ulcer reconstruction in patients with heterotopic ossification after spinal cord injury: A case series and review of literature. Issue 4 (April 2017) - Yang, Kai; Graf, Alexander; Sanger, James
Summary: Heterotopic ossification (HO) is widely recognized as a common occurrence among patients suffering from traumatic spinal cord injuries (SCI). The exact etiology of HO formation remains unknown. Published medical and surgical management strategies are often plagued with questionable effectiveness and frequent complications. There are minimal publications regarding the management strategies of HO in SCI patients as it pertains to plastic surgery. We present a case series of patients treated at our institution who underwent treatment for pressure ulcers with underlying HO to highlight the vast spectrum of clinical phenotypes present in this population. The pathophysiology, diagnostic tools, methods of prevention, and surgical management of HO are discussed here. We believe that there are two clinically relevant patterns of HO in SCI patients. A neurogenic process that occurs early after injury is usually bilateral and involves uninjured hip joints. Pressure sores that occur are related to poor joint mobility and subsequent development of pressure points. An infection-driven process in which HO development is associated with either pressure sores or septic hip joints is generally unilateral and not always associated with hip contractures. They present different challenges and reconstructive options to plastic surgeons. Although complications such as infection and HO recurrence are common, the functional and psychological benefits of restoring hip flexion are usually worthwhile.